KONTRIBUSI MAMAR TERHADAP PENDAPATAN PETANI “ Studi Kasus Di Desa Biau Kecamatan Io Kufeu Kabupaten Malaka” - Tefa, Gradiana; Seran, Wilhelmina; Un, Paulus (Wana Lestari, 2022)
This research was conducted to determine the types of mamar plants cultivated by farmers and the contribution of mamar to farmers' incomes in Biau Village, Io Kufeu District, Malaka Regency. This research was carried out in Biau Village, Io Kufeu District, Malaka Regency for 3 months, namely May-July 2021. This study used the interview method to collect research data, observation to check the data that had been obtained during interviews, literature study for secondary data collection and purposive sampling to determine the number of respondents to be interviewed. The results showed that there were 5 types of forestry plants in Mamar land, namely teak (Tectona Grandis), mahogany (Switenia Mahagoni), coconut (Cocos Nucifera), candlenut (Aleurites Moluccanus) and areca nut (Areca Catechu). There are 5 types of plantation crops, namely citrus (Citrus), mango (Mangifera Indica), cashew (Anacardium Occidentale), cocoa (Theobroma Cacao) and coffee (Coffea). Mamar's contribution to farmer's household income is 82% with a value of Rp. Rp858.846.000-/year.